Preparation method of efficient flame-retardant titanium dioxide
By introducing Mn2+ and segmented temperature-changing coating processes in the inorganic coating step of titanium dioxide, a uniform and dense aluminum film structure is formed, which solves the problems of high cost and complex process of existing flame retardant coatings, and significantly improves the flame retardant and comprehensive performance of titanium dioxide.
Patent Information
- Application Number
- CN202411720115.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
Existing indoor flame retardant coatings have problems such as high cost, complex process, poor storage stability, fire resistance and environmental protection need to be improved, and weak weather resistance and water resistance.
The inorganic coating process is adopted to introduce Mn2+ in the inorganic coating step, and the inorganic coating is carried out through a segmented temperature-changing coating process to control the formation and coating speed of the aluminum film to form a uniform and dense aluminum film structure, and improve the flame retardant performance of titanium dioxide.
It significantly improves the flame retardant performance of titanium dioxide, can quickly reduce the ignition point temperature when the fire starts, curb the spread of fire, improve the overall performance of the material, and reduce costs.
Smart Images

Figure CN119529562A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium dioxide, and in particular to a method for preparing high-efficiency flame-retardant titanium dioxide. Background Art
[0002] Indoor fire is an extremely serious accident disaster, which has thorny problems such as fast fire spread and difficulty in effective prevention. Once a fire occurs, it can often cause huge loss of life and property in a short period of time, bringing a heavy burden to society. There are many types of indoor high-temperature fire-resistant coatings commonly used in the market, among which the more common ones are intumescent fire-retardant coatings, inorganic fire-retardant coatings, and water-based fire-retardant coatings. The advantage of intumescent fire-retardant coatings is that they can expand rapidly when heated to form a thick insulation layer, effectively preventing heat transfer, thereby delaying the spread of fire to a certain extent, and buying precious time for personnel evacuation and fire extinguishing. Inorganic fire-retardant coatings are mainly composed of inorganic materials, have good high-temperature resistance and chemical stability, are not easy to burn, can maintain structural integrity in high-temperature environments, and play a role in fire prevention and heat insulation. Water-based fire-retardant coatings use water as a solvent, have the advantages of good environmental performance, non-flammability, low toxicity, etc., which are in line with the pursuit of environmentally friendly products in modern society.
[0003] CN118956212A discloses a multi-heat-resistant ultra-thin intumescent fire-retardant coating and its preparation method and application. It adopts a single-component water-based system, is environmentally and construction-friendly, has low VOC and high flash point, and uses special materials such as modified graphene oxide to overcome the dispersion problem of ordinary graphene and improve water resistance. Through the three-level insulation design and multiple composite carbon source design, the carbon layer has an excellent expansion ratio, high uniformity and density, and the fire resistance time is increased by 49%. However, this technology also has room for improvement: in practical applications, due to the use of special materials and modification methods, it may face the problem of high costs; in the face of complex and harsh environments, its performance stability and durability need to be further tested; in the long-term use process, its stability may be affected by environmental factors, resulting in a decrease in the expansion effect, and some intumescent fire-retardant coatings may release harmful gases when burning, posing a threat to the health of indoor personnel.
[0004] Cui et al. studied the preparation process of inorganic water-based fire retardant coatings. They used silica sol, resin, titanium dioxide and other raw materials to prepare color paste first, then added base materials to the color paste and stirred at low speed to disperse into color paint, and determined the process parameters by means of detection methods such as rotary viscometer, Tu-4 viscometer and precision pH test paper. However, there are some areas for improvement in this technology: the storage stability of the coating is poor, and it will separate water and precipitate after being placed for a long time. It may be due to low solid content and large particles of pigments and fillers, and the formula needs to be optimized or suitable substances need to be added to improve; in terms of process, the synergistic effect of dispersion speed and time needs to be further explored to improve quality and efficiency, while reducing dispersion energy consumption; fire retardant performance needs to be further improved; environmental protection needs to be improved in a greener direction, and the decorativeness of inorganic fire retardant coatings is relatively poor, which may not meet the needs of some places with high requirements for indoor aesthetics; at the same time, its construction process is relatively complicated, requiring professional personnel to operate, which increases the construction cost.
[0005] CN118562373A discloses a water-based environmentally friendly two-component high-temperature fireproof topcoat and a preparation method thereof, with the purpose of improving the weather resistance of water-based fireproof coatings. Component A comprises water-based silicone-modified acrylic emulsion, film-forming aid, flame-retardant filler, cosolvent and water, and component B comprises hexamethylene diisocyanate and solvent. Component A and component B have a weight ratio of 8:1, and are prepared by specific steps. However, there are some areas for improvement in this patent, such as long-term performance of weather resistance under extreme conditions, further optimization of flame retardant properties, widening of the range of raw material selection, process simplification, adaptability to special substrates and chemical environments, etc. There is still room for research and improvement. In addition, the water resistance and weather resistance of water-based fireproof coatings are relatively weak. In a humid environment or long-term exposure to the natural environment, its fireproof performance may be affected, requiring more frequent maintenance and care.
[0006] In summary, existing indoor flame-retardant coatings have the problems of high cost, complex process, poor storage stability, need to improve fire resistance and environmental protection, weak weather resistance and water resistance, and high maintenance requirements. Summary of the invention
[0007] In order to solve the problems of the prior art, the present invention provides a method for preparing a highly efficient flame retardant titanium dioxide, wherein the highly efficient flame retardant titanium dioxide is ingeniously introduced with Mn in the inorganic coating step. 2+, and adopts a segmented variable temperature coating process for inorganic coating. By cleverly controlling the pH value, the aluminum film forms a more uniform and dense structure on the surface of titanium dioxide, thereby improving the surface properties of titanium dioxide; in addition, the generation and coating speed of the aluminum film are controlled by temperature regulation. The appropriate temperature conditions can ensure the stable generation process of the aluminum film and make the coating speed moderate, which not only ensures the integrity of the coating, but also improves the coating efficiency; through a series of process improvements, the flame retardant properties of the finished titanium dioxide are greatly improved compared with similar products prepared by the prior art; when the putty powder or latex paint added with the high-efficiency flame-retardant titanium dioxide of the present invention is used for painting, the ignition point temperature can be quickly reduced at the beginning of the fire, successfully curbing the spread of the fire and preventing it from entering the full outbreak stage. In view of its excellent performance, the product has extremely broad market application prospects and commercial potential.
[0008] The specific implementation method includes the following steps:
[0009] Step 1: Particle size processing
[0010] Grinding the raw materials obtained from the rotary kiln to obtain a crude titanium dioxide product;
[0011] Step 2: Beating and Dispersion
[0012] Add the ground titanium dioxide crude product described in step 1 into water, control the concentration to be 280-320 g / L based on the mass of TiO2 in the titanium dioxide crude product, stir for 2 min, add the mixed dispersant, stir at a rate of 500-700 r / min, adjust the pH to 9.8-10.2, heat and continue stirring for 30-60 min to obtain a titanium dioxide homogeneous liquid;
[0013] Step 3: Organic coating
[0014] Add the organic coating agent to the titanium dioxide homogeneous liquid described in step 2, adjust the pH to 9-10, heat and stir for 60-90 minutes, the temperature is 60-70°C, the stirring rate is 250-500r / min, then adjust the pH to 10-10.2, raise the temperature to 60-65°C, continue stirring and maturing for 30-40 minutes, and obtain an organic-coated titanium dioxide homogeneous liquid;
[0015] Step 4: Inorganic coating
[0016] Add the inorganic coating film agent to the organic coated titanium dioxide homogeneous liquid described in step 3 in sequence, adjust the pH to 6.5-7.5, maintain the temperature at 65-70°C, continue stirring and maturing for 2-3 hours, and the stirring rate is 250-500r / min to obtain a coated product; filter the coated product, dry it at low temperature at 70°C, and obtain the high-efficiency flame retardant titanium dioxide.
[0017] Furthermore, in step 1, the grinding medium is any one of 0.8-1 mm zirconium beads, glass beads, ceramic beads, and steel beads, with a filling ratio of 50-60%.
[0018] Further, in step 1, the specific steps of grinding are:
[0019] S1, primary grinding: put titanium dioxide into a roller mill, set the linear speed to 2-5m / s, and the grinding time to 20-60min to obtain primary grinding crude titanium dioxide, D50 = 3.496μm;
[0020] S2, second-stage grinding: put titanium dioxide into a colloid ball mill, set the speed to 20-50r / min, the time to 40-60min, and obtain titanium dioxide D50 = 1.782μm;
[0021] S3, 3rd level grinding: Put the titanium dioxide into a sand mill, set the speed of the dispersing disk of the sand mill to 1600-1800 rpm, the time is 60-90 min, and obtain titanium dioxide D50 = 0.53 μm;
[0022] S4, 4th level grinding: The titanium dioxide is further ground in a sand mill, with the speed of the dispersion disk of the sand mill being 1800-2000 rpm, for 60-90 min, to obtain titanium dioxide with D50=0.457 μm.
[0023] Furthermore, in step 2, the mixed dispersant is selected from any two or three of sodium silicate, sodium hexametaphosphate, and propanolamine, and the amount of the dispersant added is 0.8-1% of the mass of the titanium dioxide based on the mass of the titanium dioxide and the total mass of the dispersant.
[0024] Furthermore, in step 3, the organic coating agent is any one of organosilicon, organosilicon and silane, and the amount of the organic coating agent added is 0.3-0.5% of the mass of the titanium dioxide based on the mass of the titanium dioxide.
[0025] 7. Further, in step 4, first add an aqueous solution of manganese salt, stir evenly, and maintain the temperature at 60-70°C; then add a NaAlO2 aqueous solution dropwise within 30-40 minutes, then add a NaAlO2 aqueous solution and an Al2(SO4)3 solution dropwise within 90-120 minutes, and then continue to add an Al2(SO4)3 solution dropwise within 30-40 minutes, and at the same time use sulfuric acid or sodium hydroxide to adjust the pH to 6.5-7.5, and continue stirring and maturing for 60-90 minutes.
[0026] Furthermore, in step 4, the aqueous solution of manganese salt is an aqueous solution of any one of MnCl2 and MnSO4.
[0027] Furthermore, in step 4, based on the mass of titanium dioxide as a percentage basis and calculated by the mass of NaAlO2, the amount of NaAlO2 added to the titanium dioxide is controlled to be 4-6% of the mass of NaAlO2; based on the mass of titanium dioxide as a percentage basis and calculated by the mass of Mn ions, the amount of manganese salt in the aqueous solution is controlled to be 0.3-0.5% of the mass of titanium dioxide; based on the mass of titanium dioxide as a percentage basis and calculated by the mass of Al2(SO4)3, the amount of Al2(SO4)3 solution is controlled to be 3-6% of the mass of titanium dioxide.
[0028] Furthermore, in step 5, the particle size of the titanium dioxide after the surface coating treatment is D50=0.486-3.502.
[0029] The beneficial effects of the present invention are as follows:
[0030] 1. The present invention introduces manganese salts to carry out inorganic coating treatment in the inorganic coating process, which unexpectedly improves the high temperature resistance of titanium dioxide. Manganese ions participate in the optimization and adjustment of the titanium dioxide crystal structure, accurately occupy specific positions inside the crystal, and form chemical bonds with aluminum salts or other ions added later, ensuring the stability of the titanium dioxide crystal structure during coating and subsequent processing, effectively avoiding structural damage or variation, and playing a key role in maintaining the stability of the physical and chemical properties of titanium dioxide; at the same time, the introduction of manganese salts prompts manganese ions to shape a specific charge distribution pattern on the surface of titanium dioxide particles. This change in charge distribution creates favorable conditions for the subsequent adsorption and deposition of coating substances such as aluminum salts on the surface of titanium dioxide, greatly improving The uniformity and density of the coating further enhance the coating effect; in the initial stage of a fire, the manganese salt and aluminum salt coating layers work synergistically to build a thermal insulation protective layer similar to a ceramic texture, which effectively prevents heat from being conducted to the internal material and effectively slows down the rate of thermal decomposition of the material, thereby significantly improving the flame retardant performance; in addition, the presence of manganese salt can also affect the thermal decomposition process of titanium dioxide at high temperatures, and strongly promote the formation of a carbon layer. This carbon layer has excellent heat insulation and oxygen isolation properties, which can effectively block the spread of force, reduce the transfer of heat and oxygen to the unburned area, and further enhance the flame retardant effect.
[0031] 2. Manganese salts and subsequently added aluminum salts and other ingredients produce a strong synergistic flame retardant effect, especially in the early stages of a fire. The redox reaction of manganese salts in a high temperature environment can work closely with substances such as aluminum oxide formed by aluminum salts to strongly inhibit heat conduction reactions, significantly improving the flame retardant efficiency of the entire system, thereby enabling titanium dioxide to achieve excellent flame retardant effects at a relatively low addition amount, which not only effectively reduces costs, but also greatly improves the overall performance of the material.
[0032] 3. The preparation method of high-efficiency flame-retardant titanium dioxide adopted in the present invention not only significantly enhances the flame retardant properties of titanium dioxide, but also has the outstanding advantages of easy operation and good controllability. Moreover, the titanium dioxide has the excellent characteristic of high flame retardancy on the basis of conventional application properties such as whiteness and hiding power, which has opened up a new development direction for the titanium dioxide industry and promoted the innovation and progress of the industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The particle size distribution diagram (primary particle size distribution diagram) of Example 1 and Comparative Example 1 of the present invention;
[0034] Figure 2 The particle size distribution diagram (secondary particle size distribution diagram) of Example 2 and Comparative Example 2 of the present invention;
[0035] Figure 3 The particle size distribution diagram (three-level particle size distribution diagram) of Example 3 and Comparative Example 3 of the present invention;
[0036] Figure 4 This is a TEM image of the finished product of Example 1 of the present invention;
[0037] Figure 5 This is a TEM image of the finished product of Example 2 of the present invention;
[0038] Figure 6 This is a TEM image of the finished product of Example 3 of the present invention;
[0039] Figure 7 This is the TEM image of the finished product of Example 4 of the present invention. DETAILED DESCRIPTION
[0040] Step 1: Particle size processing
[0041] The grinding media uses 0.8mm zirconium beads, with a filling ratio of 60%;
[0042] 4000g of the titanium dioxide raw material obtained in the rotary kiln was put into a roller mill, and the linear speed was set to 2m / s for 60min to obtain a primary grinding crude titanium dioxide with D50=3.496μm. 1000g was taken out and recorded as crude product 1; the rest was subjected to secondary grinding;
[0043] 3000g of primary-grinded crude titanium dioxide was put into a colloidal ball mill, and the speed was set to 20r / min for 60min to obtain secondary-grinded crude titanium dioxide, D50 = 1.782μm. 1000g was taken out and recorded as crude product 2; the rest was subjected to tertiary grinding;
[0044] 2000g of the secondary ground crude titanium dioxide was put into a sand mill, and the speed of the dispersion disk of the sand mill was set to 1800rpm for 120min to obtain the tertiary ground crude titanium dioxide, D50 = 0.53μm, 1000g was taken out and recorded as crude product 3; the rest was subjected to the fourth-stage grinding;
[0045] 1000 g of the third-grade crude titanium dioxide powder was further ground in a sand mill, with the speed of the dispersion disk of the sand mill being 2000 rpm for 120 min to obtain a fourth-grade crude titanium dioxide powder with D50 = 0.457 μm, which was recorded as crude product 4;
[0046] The four-stage ground crude titanium dioxide 1-4 is divided into two equal parts, respectively recorded as A1, A2, A3, A4 and B1, B2, B3, B4; A1-A4 are treated by the surface coating activation treatment method of the present invention as Examples 1-4; B1-B4 are treated by the traditional single variable method as Comparative Examples 1-4.
[0047] Examples 1-4
[0048] Step 2: Beating and Dispersion
[0049] The crude titanium dioxide A1-A4 described in step 1 is added into water respectively, and the concentration is controlled to be 300 g / L based on the mass of TiO2 in the crude titanium dioxide. After stirring for 2 min, 45 mL of a 100 g / L Na2SiO3 solution is added, and the stirring rate is 500 r / min. The pH is adjusted to 10, and heating and stirring are continued for 30 min to obtain titanium dioxide homogeneous liquid A1-A4;
[0050] Step 3: Organic coating
[0051] 1.5 g of organosilicon SB-201 (Suzhou Hualian High-tech Ceramic Materials Co., Ltd.) was added to the titanium dioxide homogeneous liquid A1-A4 described in step 2, and a 20 wt % NaOH solution was added dropwise to adjust the pH to 9, and the mixture was heated and stirred for 60 min at a temperature of 60° C. and a stirring rate of 300 r / min. Then, a 20 wt % NaOH solution was added dropwise to adjust the pH to 10, and the mixture was heated to 63.4° C. and stirred and matured for 30 min to obtain organically coated titanium dioxide homogeneous liquids A1-A4;
[0052] Step 4: Inorganic coating
[0053] 15 mL of 100 g / L MnSO4 aqueous solution was added dropwise to the organic-coated titanium dioxide homogeneous liquid A1-A4 described in step 3, stirred evenly, and the temperature was maintained at 65°C; then 35 mL of 150 g / L NaAlO2 aqueous solution was added dropwise within 30 min, and then 100 mL of 150 g / L NaAlO2 aqueous solution and 82 mL of 150 g / L Al2(SO4)3 solution were added dropwise within 90 min. liquid, and then continue to drop 51mL of 150g / L Al2(SO4)3 solution within 30min, and use 10wt% sulfuric acid to adjust pH=6.7, maintain the temperature at 65°C, continue stirring and aging for 2h, and the stirring rate is 300r / min to obtain coated products A1-A4; the coated products A1-A4 are filtered respectively, and low-temperature dried at 70°C to obtain the high-efficiency flame retardant titanium dioxide, which are recorded as finished products A1-A4, and their D50 particle sizes are shown in Table 1.
[0054] Table 1. D50 data of crude titanium dioxide products 1-4 after four-stage grinding, finished products A1-A4 of Examples 1-4, and finished products of Comparative Examples B1-B4.
[0055] sample D50(μm) sample D50(μm) sample D50(μm) Crude product 1 3.496 Finished product A1 3.502 Finished product B1 3.515 Crude product 2 1.782 Finished product A2 1.805 Finished product B2 1.817 Crude product 3 0.53 Finished product A3 0.565 Finished product B3 0.642 Crude product 4 0.457 Finished A4 0.486 Finished product B4 0.463
[0056] Comparative Examples 1-4
[0057] Beating and dispersion: Take the aforementioned titanium dioxide crude products B1-B4 and add them into water respectively, adjust the pH to 10.5 with 100 g / L Al2(SO4)3 crystals, maintain the temperature at 60°C, stir for 2 min, and obtain titanium dioxide slurry, prepare 200 g / L Na2SiO3 solution and 100 g / L sodium hexametaphosphate solution into a mixed solution in a mass ratio of 1:5, add 3 g of the mixed solution into the titanium dioxide slurry, stir for 30 min, and the stirring rate is 350 r / min to obtain a titanium dioxide homogeneous liquid;
[0058] Inorganic coating: Add 100mL of 100g / L NaSiO3 solution to the titanium dioxide homogeneous liquid within 1.5h, set the temperature to 85±3℃, stir and mature for 0.5h after the addition is completed, and the stirring rate is 350r / min; then add 10wt% H2SO4 solution within 3.5h, mature for 0.5h, control pH=9, add Al2(SO4)3 solution with a concentration of 100g / L, adjust pH=2, and continue to stir and mature for 0.5h after dropping; continue to add 120mL of 100g / L NaAlO2 solution within 2h, continue stirring, and the stirring rate is 600r / min. Use NaOH solution or H2SO4 solution to adjust pH=7 to obtain finished products B1-B4, whose D50 particle size is shown in Table 1.
[0059] Performance Test:
[0060] The SCX value of titanium dioxide refers to the color tone of titanium dioxide in black slurry after grinding with black slurry. The specific method is as follows: take 3g of titanium dioxide finished products A1, A2, A3, A4 and B1, B2, B3, B4 and 3g of standard black slurry respectively, mix and apply them on a flat grinder, grind twice, 50 turns each time, to obtain the sample to be tested, then take the sample to be tested on the flat grinder, and use a 60μm wet film preparation device to scrape on the glass plate to obtain the sample to be tested; the composition of the standard black slurry is linseed oil (Harbin Paint Factory), castor oil (Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd.), carbon black (Japan Mitsubishi MA100), and fumed silica (Evonik) in a ratio of 680:170:18.5:30, and the viscosity value is 1000s; use a spectrocolorimeter (Agera, HunterLab) to measure the three stimulus values X, Y, and Z of each sample to be tested; the standard value X of the three stimulus values is obtained after the spectrocolorimeter is calibrated 标 , Y 标 , Z 标 , calculate the TCS value and SCX value of each sample to be tested according to the following formula:
[0061] TCS=TCS 标 -(Y 标 -Y)×100
[0062] SCX=(ZX)-SCX 标
[0063] Table 2. Finished pigment indicators of Examples 1-4.
[0064] sample L a b TCS SCX A1 95.44 -1.15 1.88 2030 3.71 A2 95.47 -1.15 1.84 2030 3.68 A3 95.52 -1.13 1.63 2040 4.22 A4 95.57 -1.14 1.66 2050 4.15
[0065] Table 3. Finished pigment indicators of Comparative Examples 1-4.
[0066] sample L a b TCS SCX B1 95.68 -1.06 1.72 2060 3.59 B2 95.75 -1.11 1.72 2050 3.63 B3 95.79 -1.09 1.72 2050 3.65 B4 95.83 -1.09 1.71 2050 3.85
[0067] Flame retardant performance test
[0068] Take 3g of titanium dioxide finished products A1, A2, A3, A4 and B1, B2, B3, B4 respectively, mix them and apply them on a flat grinder, grind them twice, 50 turns each time, to obtain the sample to be tested, then take the sample to be tested on the flat grinder, use a 60μm wet film preparation device to scrape on the glass plate to obtain the sample to be tested; the viscosity value is 100s; put the sample to be tested into an oven, set the automatic heating program, the heating rate is 2℃ / min, use a spectrocolorimeter (Agera, HunterLab) to measure the L, a, b values of each sample every 20℃ from 65℃, and measure the L, a, b values of each sample every 10℃ after exceeding 125℃, and get the L after calibration of the spectrocolorimeter. 标 、a标 、b 标 The value is taken as the standard value;
[0069] The ΔE value of titanium dioxide is an important indicator to measure its color difference or color change degree. It is of key significance in the production, application and quality control of titanium dioxide. The ΔE value is used to quantify the difference between two colors, so the smaller the value, the better. In the titanium dioxide industry, it is generally believed that a ΔE value less than 0.3 indicates good whiteness. In the International Commission on Illumination (CIE) "Lab" color space, it is determined by calculating the distance between the standard color and the actual measured color. The CIELab color space is designed based on the uniformity of the human eye's perception of color and can more accurately describe color differences. Its formula is:
[0070]
[0071] The CIELab color space is based on the theory of opposing colors and describes colors through three coordinate axes:
[0072] L (brightness): represents the lightness or darkness of the color, ranging from 0 (black) to 100 (white). The larger the value, the brighter the color.
[0073] a (red-green axis): positive values indicate the red direction, negative values indicate the green direction, and 0 indicates neutral color (no red-green bias);
[0074] b (yellow-blue axis): positive values indicate yellow direction, negative values indicate blue direction, and 0 indicates neutral color (no yellow-blue bias); the ΔE values of Examples 1-4 and Comparative Examples 1-4 during the heating process are calculated according to formula (1) and are shown in Table 4.
[0075] Table 4. ΔE values during the heating process of Examples 1-4 and Comparative Examples 1-4.
[0076] sample ΔE(65℃) ΔE(85℃) ΔE(105℃) ΔE(125℃) ΔE(135℃) ΔE(145℃) A1 0.15 0.23 0.27 0.29 0.35 0.49 B1 0.16 0.21 0.32 A2 0.16 0.19 0.24 0.36 B2 0.14 0.18 0.37 A3 0.13 0.21 0.34 B3 0.15 0.36 0.46 A4 0.16 0.26 0.42 B4 0.14 0.31 0.43
[0077] At the same time, observe the color of each sample with the naked eye. If the sample is obviously yellow, it proves that the sample has reached the high temperature resistance limit, which is recorded in Table 5.
[0078] Table 5. Records of obvious color changes of titanium dioxide observed after temperature resistance test
[0079] sample 65° 85° 105° 125° 135° 145° A1 √ √ √ √ × × B1 √ √ × A2 √ √ √ × B2 √ √ × A3 √ √ × B3 √ × × A4 √ √ × B4 √ × ×
[0080] As shown in the data of Table 4, the flame retardant effect of primary grinding is the best. Therefore, when using the method of the present invention to prepare high-efficiency flame retardant titanium dioxide, there is no need for excessive grinding. The finished titanium dioxide with large particle size (Example 1) has the best temperature resistance.
[0081] The present invention introduces manganese salt in the inorganic coating process for inorganic coating treatment, and adopts a segmented variable temperature coating process for inorganic coating, which allows the aluminum film to form a more uniform and dense structure on the surface of titanium dioxide. Compared with comparative examples 1-4, the present invention unexpectedly improves the high temperature resistance of titanium dioxide. This is because manganese ions participate in the optimization and adjustment of the titanium dioxide crystal structure, and the manganese salt and aluminum salt coating layer work synergistically, thereby significantly improving the flame retardant performance.
[0082] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. A method for preparing a highly efficient flame retardant titanium dioxide, characterized in that: The following steps are involved: Step 1: Particle size processing Grinding the raw materials obtained from the rotary kiln to obtain a crude titanium dioxide product; Step 2: Beating and Dispersion Add the ground titanium dioxide crude product described in step 1 into water, control the concentration to be 280-320 g / L based on the mass of TiO2 in the titanium dioxide crude product, stir for 2 min, add the mixed dispersant, stir at a rate of 500-700 r / min, adjust the pH to 9.8-10.2, heat and continue stirring for 30-60 min to obtain a titanium dioxide homogeneous liquid; Step 3: Organic coating Add the organic coating agent to the titanium dioxide homogeneous liquid described in step 2, adjust the pH to 9-10, heat and stir for 60-90 minutes, the temperature is 60-70°C, the stirring rate is 250-500r / min, then adjust the pH to 10-10.2, raise the temperature to 60-65°C, continue stirring and maturing for 30-40 minutes, and obtain an organic-coated titanium dioxide homogeneous liquid; Step 4: Inorganic coating The inorganic coating film agent is sequentially added to the organically coated titanium dioxide homogeneous liquid described in step 3, the pH is adjusted to 6.5-7.5, the temperature is maintained at 65-70° C., and stirring is continued for 2-3 hours at a stirring rate of 250-500 r / min to obtain a coated product; The coated product is filtered and dried at low temperature at a temperature of 70-90° C. to obtain a highly efficient flame retardant titanium dioxide.
2. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 1, characterized in that: In step 1, the grinding medium is any one of 0.8-1 mm zirconium beads, glass beads, ceramic beads, and steel beads, with a filling ratio of 50-60%.
3. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 1, characterized in that: In step 1, the specific steps of grinding are: the titanium dioxide is sequentially passed through a roller mill with a linear speed of 2-5m / s for 20-60min, a colloid mill with a rotation speed of 20-50r / min for 40-60min, and a sand mill with a dispersion disk speed of 1600-2000rpm for 60-90min.
4. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 1, characterized in that: In step 1, titanium dioxide particles with a particle size of D50=0.457-3.496 μm are obtained after grinding.
5. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 1, characterized in that: In step 2, the mixed dispersant is selected from any two or three of sodium silicate, sodium hexametaphosphate, and propanolamine, and the amount of the dispersant added is 0.8-1% of the mass of the titanium dioxide based on the mass of the titanium dioxide and the total mass of the dispersant.
6. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 1, characterized in that: In step 3, the organic coating agent is any one of organic silicon film, organic silicon and silane, and the amount of the organic coating agent added is 0.3-0.5% of the mass of the titanium dioxide based on the mass of the titanium dioxide.
7. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 1, characterized in that: In step 4, first add an aqueous solution of manganese salt, stir evenly, and maintain the temperature at 60-70°C; then add a NaAlO2 aqueous solution dropwise within 30-40 minutes, then add a NaAlO2 aqueous solution and an Al2(SO4)3 solution dropwise within 90-120 minutes, then continue to add an Al2(SO4)3 solution dropwise within 30-40 minutes, and at the same time use sulfuric acid or sodium hydroxide to adjust the pH to 6.5-7.5, and continue stirring and maturing for 60-90 minutes.
8. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 7, characterized in that: In step 4, the aqueous solution of manganese salt is an aqueous solution of any one of MnCl2 and MnSO4.
9. The method for preparing a highly efficient flame retardant titanium dioxide according to any one of claims 1 or 7, characterized in that: In step 4, based on the mass of titanium dioxide as a percentage basis and calculated by the mass of NaAlO2, the amount of NaAlO2 added to the titanium dioxide is controlled to be 4-6% of the mass of titanium dioxide; based on the mass of titanium dioxide as a percentage basis and calculated by the mass of Mn ions, the amount of manganese salt in the aqueous solution is controlled to be 0.3-0.5% of the mass of titanium dioxide; based on the mass of titanium dioxide as a percentage basis and calculated by the mass of Al2(SO4)3, the amount of Al2(SO4)3 solution is controlled to be 3-6% of the mass of titanium dioxide.
10. The method for preparing a highly efficient flame retardant titanium dioxide according to claim 1, characterized in that: In step 5, the particle size of the titanium dioxide after the surface coating treatment is D50=0.486-3.502 μm.